Catalyst for catalytic dehydrogenation of formic acid as well as preparation method and application of catalyst
By modifying nitrogen, phosphorus and boron groups on chromium metal organic framework materials and supporting nanopalladium and chromium, PdCr-NPB-Cr-MOF catalyst was prepared, which solved the catalytic activity and selection of existing catalysts under near room temperature conditions. The problem of insufficient properties has achieved efficient formic acid catalyzed dehydrogenation reaction.
Patent Information
- Application Number
- CN202411524378.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The existing catalysts used for formic acid catalytic dehydrogenation have insufficient catalytic activity and selectivity under near room temperature conditions, making it difficult to meet the efficient storage and release requirements of hydrogen.
The nanopalladium-based catalyst PdCr-NPB-Cr-MOF was prepared by impregnation-reduction method using a chromium metal organic framework material modified with nitrogen, phosphorus and boron groups as the support.
A catalytic dehydrogenation reaction with high activity, high hydrogen selectivity and low carbon monoxide selectivity was achieved under near room temperature. The hydrogen selectivity reached 100%, the formic acid conversion rate reached more than 95%, and the catalyst stability after repeated use was achieved. good.
Smart Images

Figure BDA0005108799830000051 
Figure HDA0005108799850000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage material preparation methods, and specifically relates to a catalyst for catalytic dehydrogenation of formic acid and a preparation method and application thereof. Background Art
[0002] As the global demand for clean energy grows, energy storage and conversion technology has become a research focus. Among the many energy storage solutions, hydrogen energy has attracted much attention due to its high energy density and clean and environmentally friendly characteristics. However, the storage and release of hydrogen has always been a key problem that restricts the widespread application of hydrogen energy.
[0003] As a new hydrogen storage method, liquid organic hydrogen carriers have similar properties to gasoline and diesel, and are easy to transport and distribute, and are compatible with existing infrastructure. Formic acid, because of its stability, non-toxicity, low explosion and fire hazards, is one of the most promising liquid organic hydrogen carriers. Although the hydrogen capacity of formic acid (4.4wt.%, 53.4g / L) is slightly lower than that of some liquid organic hydrogen carriers, the dehydrogenation of formic acid is much easier than other liquid organic hydrogen carriers and can be carried out at lower temperatures. In addition, the products of formic acid dehydrogenation are in the gas phase, which effectively prevents the accumulation of by-products. The CO2 produced by formic acid can also be recycled to prepare formic acid, thereby achieving a theoretical zero CO2 emission process. Formic acid can also be prepared by biomass oxidation, which is a renewable source of formic acid. Due to these advantages, formic acid dehydrogenation has received increasing attention in recent years. The development of liquid organic hydrogen carrier dehydrogenation catalysts with excellent performance is the key to promoting the large-scale application of hydrogen energy.
[0004] Catalysts used for formic acid dehydrogenation can be divided into homogeneous catalysts and heterogeneous catalysts. The former usually exhibits high catalytic activity, but its stability is not good enough and it is difficult to separate and recover, which greatly limits its industrial application. Heterogeneous catalysts have attracted great interest due to their good stability. However, the currently popular heterogeneous catalysts for formic acid dehydrogenation are mainly based on precious metals with low abundance and high cost. Although some non-precious metal-based catalysts for formic acid dehydrogenation have been reported, these catalysts usually require relatively high catalytic temperatures and have low selectivity. Therefore, the development of an efficient catalyst for formic acid dehydrogenation that can achieve high-activity and high-selectivity dehydrogenation reactions under near-room temperature conditions is of great significance for promoting the development of hydrogen energy and the application of formic acid in the field of hydrogen storage. Summary of the invention
[0005] The technical problem to be solved by the present invention is to prepare a formic acid catalytic dehydrogenation catalyst with high activity, high hydrogen selectivity and low carbon monoxide selectivity suitable for near room temperature reaction conditions, so that the hydrogen produced by formic acid catalytic dehydrogenation can better meet the requirements of long-life operation of fuel cell electrodes. In order to solve the above problems, the present invention provides a catalyst for formic acid catalytic dehydrogenation and a preparation method and application thereof. Through experimental verification, the catalyst for formic acid catalytic dehydrogenation meets the above requirements.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] The catalyst for catalytic dehydrogenation of formic acid of the present invention is a catalyst which uses a chromium metal organic framework material modified by nitrogen, phosphorus and boron groups as a carrier and uniformly loads nano-palladium and chromium;
[0008] Wherein, according to the mass ratio, nano palladium: chromium = (1-2.5): 1; the loading rate is: the loading rate of nano palladium is 0.5-20wt%, and the loading rate of chromium is 0.5-15wt%.
[0009] The catalyst for catalytic dehydrogenation of formic acid uses a chromium metal organic framework material as a carrier, is modified by heteroelement groups, and then prepared by an impregnation-reduction method to obtain a nano palladium-based catalyst (denoted as: PdCr-NPB-Cr-MOF); the heteroelement is nitrogen, phosphorus and boron.
[0010] The catalyst for catalytic dehydrogenation of formic acid comprises the following main chemical components by mass percentage according to X-ray energy spectrum analysis: C is 40-55%, O is 20-35%, Pd is 0.5-20%, Cr is 0.5-15%, N is 2-6%, P is 1-8%, B is 1-8%, and the remainder is ignition loss and unavoidable impurities, and the percentage content of each impurity is less than 1%.
[0011] A method for preparing a catalyst for catalytic dehydrogenation of formic acid according to the present invention comprises the following steps:
[0012] S1: Hetero-element group modification
[0013] (1) mixing a chromium metal organic framework material, nitric acid and sulfuric acid at -20 to 0°C and stirring for 5 to 8 hours to obtain a mixture; after the reaction of the mixture is completed, cooling, solid-liquid separation, washing the solid product with deionized water, and then vacuum drying to obtain NO2-Cr-MOF;
[0014] Stannous chloride and NO2-Cr-MOF are stirred in an ethanol solution at 55-75°C for 6-10 hours, centrifuged, and the obtained solid product is washed with hydrochloric acid and ultrasonic combined with distilled water, and then dried again at high temperature and in vacuum to obtain N-Cr-MOF;
[0015] In (1) of S1, the mass ratio of chromium metal organic framework material: nitric acid: sulfuric acid is 1: (70-112): (75-130).
[0016] In the above-mentioned S1 (1), the cooling temperature is -10 to 5°C.
[0017] In the step (1) of S1, the vacuum drying is performed at a pressure of 0.95 to 0.98 atm and a temperature of 40 to 70° C. for 8 to 16 hours.
[0018] In (1) of S1, the mass ratio of stannous chloride:NO2-Cr-MOF is (25-85):1; the solid-liquid ratio of stannous chloride+NO2-Cr-MOF:ethanol is 1 g:(5.5-8.5) mL.
[0019] In the above-mentioned S1 (1), the temperature of high-temperature vacuum drying is 130 to 170°C.
[0020] (2) placing N-Cr-MOF in N,N-dimethylformamide solvent, heating and reflux at 65° C. for 30 to 40 minutes, adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continuing heating and reflux, reacting for more than 12 hours, removing N,N-dimethylformamide, washing with acetonitrile and water and recrystallizing to obtain precipitated NP-Cr-MOF;
[0021] In the above-mentioned S1 (2), the added amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide accounts for 30-60% by mass of N-Cr-MOF.
[0022] (3) Mixing monoethanolamine borate (MEB) and anhydrous ethanol, stirring until the monoethanolamine borate is completely dissolved, adding NP-Cr-MOF, stirring evenly at room temperature, reacting for 10 to 15 hours, separating the solid and the liquid, washing the obtained precipitate with ethanol to remove impurities, and vacuum drying to obtain NPB-Cr-MOF;
[0023] In (3) of S1, the mass ratio of monoethanolamine borate (MEB):NP-Cr-MOF=(0.3-0.5):1.
[0024] In (3) of S1, the amount of anhydrous ethanol used is sufficient to dissolve monoethanolamine borate.
[0025] S2: Nano-palladium-based catalyst (PdCr-NPB-Cr-MOF) prepared by impregnation-reduction method
[0026] NPB-Cr-MOF and deionized water were mixed and ultrasonicated for 30 to 40 minutes to obtain a carrier solution;
[0027] With stirring, Na2PdCl4 and Cr(NO3)3·9H2O are dropped into the carrier solution, and stirring is continued for 2 to 3 hours. NaBH4 solution is added and stirring is continued for 30 to 50 minutes. The solid-liquid separation is performed, and the filter membrane with the precipitate is freeze-dried. After removing the filter membrane, PdCr-NPB-Cr-MOF is obtained.
[0028] In the S2, the ultrasonic frequency is 30 to 50 KHz, and the ultrasonic time is 30 to 60 minutes.
[0029] In the S2, according to the solid-liquid ratio, NPB-Cr-MOF: water = 1g: (200-300)mL.
[0030] In the S2, the amount of chromium nitrate nonahydrate solution added is 15-25% by volume of the carrier solution, and the amount of Na2PdCl4 solution added is 18-40% by volume of the carrier solution;
[0031] The molar concentration of the chromium nitrate nonahydrate solution is 0.01-0.035 mol / L, and the dripping rate is 0.5-3 mL / min;
[0032] The molar concentration of the Na2PdCl4 solution is 0.02-0.03 mol / L, and the dripping rate is 1-1.5 mL / min;
[0033] In the S2, the amount of NaBH4 solution added is 35-50% of the volume percentage of the carrier solution, and the molar concentration of the NaBH4 solution is 0.3-0.4 mol / L.
[0034] In the above-mentioned S2, freeze drying is freeze drying at -50 to -60°C for 8 to 12 hours.
[0035] The chromium metal organic framework material is prepared by a hydrothermal method, and the preparation process includes:
[0036] Step 1: Mix chromium salt, terephthalic acid, hydrofluoric acid and deionized water, add into a high pressure reactor, react at 160-230° C. for 8-12 hours, cool naturally to room temperature, separate solid from liquid, wash, and obtain a solid product;
[0037] Step 2: placing the solid product in an ammonium fluoride solution, soaking it, and centrifuging it to obtain a solid substance; washing the solid substance with deionized water to remove impurities, and vacuum activating it to obtain a chromium metal organic framework material, which is recorded as Cr-MOF;
[0038] In the step 1, the molar ratio of terephthalic acid, chromium in chromium salt, hydrofluoric acid, and deionized water is 1:(1-3):(0.12-0.35):(25-30).
[0039] In the step 1, the chromium salt is selected from one or more of CrCl3, Cr2(SO4)3·6H2O, Cr(NO3)·9H2O, and C6H9O6Cr.
[0040] In the step 2, the molar concentration of the ammonium fluoride solution is 0.5-2 mol / L, and according to the solid-liquid ratio, the solid product: ammonium fluoride solution = 1 g: 6-10 mL;
[0041] In step 2, the soaking temperature is 60-90°C, the soaking time is more than 24 hours, the centrifugal separation speed is 6000-10000r / min, the centrifugal time is 10-15min, and the vacuum activation temperature is 150-180°C, and the vacuum activation time is 8-20h.
[0042] The invention discloses an application of a catalyst for catalytic dehydrogenation of formic acid, which is to use PdCr-NPB-Cr-MOF as a catalyst for catalytic dehydrogenation of formic acid.
[0043] The catalyst for catalytic dehydrogenation of formic acid is used as follows: at 25-70° C., more preferably 25-30° C., the catalyst for catalytic dehydrogenation of formic acid (PdCr-NPB-Cr-MOF) is contacted with formic acid to perform catalytic dehydrogenation of formic acid.
[0044] The composite catalyst for catalytic dehydrogenation of formic acid is used as a catalyst to carry out continuous catalytic dehydrogenation of formic acid. The reaction conditions are: stirring the reaction at 25-70° C. and normal pressure, collecting the produced hydrogen, and continuously adding formic acid dropwise during the reaction. The dropping speed of formic acid is converted according to the amount of hydrogen produced, that is, the amount of formic acid consumed in producing hydrogen is the amount of formic acid added.
[0045] In the application, the stirring speed of the stirring reaction is 400-800 r / min.
[0046] The TOF of the catalyst for catalytic dehydrogenation of formic acid is 1460-6150h -1 , where TOF is 1460-1620h at 25-30℃ catalytic conditions -1 The hydrogen selectivity was 100% and the formic acid conversion rate was 92-98.6%. After repeated use for three times, the formic acid conversion rate did not decrease, and the mass content of CO in the product was <0.5ppm.
[0047] The catalyst for catalytic dehydrogenation of formic acid of the present invention and its preparation method and application have the following beneficial effects:
[0048] 1) This catalyst can achieve the number of reactions occurring per unit time on each active center under near room temperature conditions (TOF can reach 1620h -1 , which is higher than the TOF value of the catalyst used for catalytic dehydrogenation of formic acid under the same reaction temperature conditions reported so far. It can also achieve a hydrogen selectivity of 100% and a formic acid conversion rate of more than 95%.
[0049] 2) Through comparative experimental studies, it was found that the concentration of carbon monoxide in the formic acid catalytic dehydrogenation catalyst prepared by the present invention was lower than the detection limit of gas chromatography (0.5 ppm) after repeated use, which shows that the catalyst has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The present invention is a device diagram for the catalytic dehydrogenation of formic acid, wherein: 1: syringe; 2: two-necked round-bottom flask; 3: water bath; 4: digital constant temperature magnetic stirrer; 5: thermocouple; 6: double-headed sampling gas measuring tube; 7: level bottle. DETAILED DESCRIPTION
[0051] The present invention is further illustrated below with examples, but the present invention is not limited thereto.
[0052] The catalyst used for catalytic dehydrogenation of formic acid contains hydrogen element. The catalyst used for catalytic dehydrogenation of formic acid uses X-ray energy spectrum to analyze the chemical composition of the catalyst, but cannot analyze the hydrogen composition. Therefore, the component structure does not contain H element.
[0053] Example 1
[0054] The preparation method of PdCr-NPB-Cr-MOF catalyst comprises the following steps:
[0055] (1) 2.4009 g of chromium nitrate nine hydrate and 0.9968 g of terephthalic acid were dissolved in 28.8 mL of deionized water, and 0.3 mL of hydrofluoric acid (mass concentration of 40%) was added to a Teflon-lined stainless steel autoclave and reacted at 200 ° C for 8 hours. After natural cooling, the solid product was filtered with a filter membrane, and then washed with ethanol 3 times. After that, the solid product was placed in 30 mL of 1 mol / L ammonium fluoride solution and soaked at 70 ° C for 24 hours. Then, it was centrifuged at 8000 r / min for 10 minutes, the supernatant was poured out, the solid product on the centrifuge tube was dispersed with deionized water, filtered with a filter membrane, and then washed with deionized water 3 times, and finally vacuum activated at 150 ° C for 8 hours to obtain a chromium-based MOF material (called Cr-MOF).
[0056] (2) 0.1 g of Cr-MOF was added to a mixture containing 7 mL of sulfuric acid and 5 mL of nitric acid, and then the beaker was placed in an electromagnetic stirring ice bath at 100 r / min and stirred for 5 hours. The mixture was then added to a 100 mL beaker containing 50 mL of ice cubes, and then filtered with a filter membrane, and then washed with deionized water for 3 times. The solid product on the filter membrane was vacuum dried at 50 ° C for 8 hours to obtain a sample (called NO2-Cr-MOF).
[0057] Then, 3.26 g of stannous chloride and 0.1 g of NO2-Cr-MOF were added to a container containing 20 mL of ethanol. The mixture was stirred at 70 ° C for 6 hours at a stirring rate of 200 r / min, and then centrifuged at 8000 r / min for 10 minutes in a high-speed centrifuge. The solid product on the inner wall of the centrifuge tube was washed with 20 mL of 36% concentrated hydrochloric acid and added to a glass container, and then the glass container was placed in an ultrasonic cleaning device for 10 minutes. Then, it was filtered with a filter membrane with a pore size of 0.22 microns, and the solid on the filter membrane was washed 3 times with distilled water. Finally, a yellow-green powder (called N-Cr-MOF) was obtained after vacuum drying at 150 ° C.
[0058] (3) 0.8 g of the prepared N-Cr-MOF was added to a 100 mL round-bottom flask equipped with a magnetic stirring device and a condenser, and 50 mL of N, N-dimethylformamide was added. The mixture was heated to reflux at 65 °C for 30 min, and 0.36 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added and continued to be heated to reflux. After reacting for 12 h, N, N-dimethylformamide was removed by rotary evaporation, and the mixture was washed and recrystallized with acetonitrile and water, respectively, to obtain a precipitated solid powder (called NP-Cr-MOF).
[0059] (4) Add 0.25 g of monoethanolamine borate (MEB) and 50 mL of anhydrous ethanol to a round-bottom flask equipped with a stirring device, stir until the MEB is completely dissolved, and then add 0.6 g of NP-Cr-MOF. After the addition of the drugs is completed, stir at room temperature. After reacting for 12 hours, filter the precipitate, wash with a small amount of ethanol to remove excess impurities, and place it in a vacuum oven at 60°C to dry for 12 hours to obtain a solid product (called NPB-Cr-MOF).
[0060] (5) 0.0400 g of NPB-Cr-MOF was dispersed in 10 mL of deionized water and ultrasonically treated for 40 minutes. Then, 2.4 mL of 0.025 mol / L Na2PdCl4 and 2 mL of 0.020 mol / L Cr(NO3)3·9H2O were added to the mixture under magnetic stirring at 300 r / min and stirred for 2 hours. Then, 3.5 mL of 0.3 mol / L NaBH4 solution was added and evenly dropped into the mixture and stirred for 30 minutes at a stirring rate of 600 r / min. The mixture was filtered with a 0.22 μm pore size filter membrane, and then the filter membrane was placed in an evaporating dish and freeze-dried in a freeze dryer for 8 hours. The catalyst (called PdCr-NPB-Cr-MOF) on the filter membrane was scraped off for later use.
[0061] The chemical composition of the catalyst is as follows:
[0062] Table 1 Chemical composition of PdCr-NPB-Cr-MOF catalyst
[0063]
[0064] An application of formic acid catalytic dehydrogenation, a formic acid catalytic dehydrogenation device is built in the laboratory, the device diagram is shown in Figure 1 , wherein a two-necked round-bottom flask 2 is placed on a digital display constant temperature magnetic stirrer 4, a thermocouple 5 connected to the digital display constant temperature magnetic stirrer 4 is placed in a heated solvent in a water bath 3 to detect the temperature of the catalytic dehydrogenation reaction, the upper bottle mouth of the two-necked round-bottom flask 2 is connected to a syringe 1, the other bottle mouth is connected to a double-headed sampling gas volume 6, and the other end of the double-headed sampling gas volume 6 is connected to a level bottle 7. To put 46 mg of the prepared PdCr-NPB-Cr-MOF catalyst into the two-necked round-bottom flask 2, add 2.5 mL of deionized water and a magnetic rotor, and move the reaction device as Figure 1 Connect, draw 2mL of formic acid solution with a concentration of 1mol / L into the syringe 1, set the reaction temperature of the digital display constant temperature magnetic stirrer 4 to 25°C, and set the magnetic stirring to 600r / min. When the water bath reaches the set temperature, inject the formic acid solution to start the reaction and start timing. Record the volume of gas generated every 30 seconds. If the volume does not change for 3 consecutive minutes, the reaction is considered to be over. The gas collected in the gas collecting pipe is analyzed by gas chromatography for its composition. The gas chromatograph uses a thermal conductivity detector (TCD) and a methane converter with a hydrogen ion flame detector to analyze the gas composition of carbon dioxide, hydrogen and carbon monoxide. The gas composition is calibrated by the standard gas prepared by Jinan Deyang Special Gas Co., Ltd., and the standard gas composition is: 49.7% H2, 50.3% CO2, 5.25ppm CO.
[0065] After analysis and testing, the gas composition after the reaction was: 0ppm CO, 50.05% H2, 49.95% CO2. The conversion rate of formic acid was 96.5%. The initial TOF of the catalyst was 1580h -1 .
[0066] Example 2
[0067] The preparation process of the catalyst was the same as in Example 1, except that the reaction temperature of the catalyst for catalytic dehydrogenation of formic acid was changed to 40° C., and other conditions remained unchanged.
[0068] After analysis and testing, the gas composition after the reaction was: 0ppm CO, 50.07% H2, 49.93% CO2. The conversion rate of formic acid was 96.8%. The initial TOF of the catalyst was 2285h -1 .
[0069] Example 3
[0070] The preparation process of the catalyst was the same as in Example 1, except that the reaction temperature of the catalyst for catalytic dehydrogenation of formic acid was changed to 50° C., and other conditions remained unchanged.
[0071] After analysis and testing, the gas composition after the reaction was: 0ppm CO, 50.02% H2, 49.98% CO2. The conversion rate of formic acid was 97.5%. The initial TOF of the catalyst was 4160h -1 .
[0072] Example 4
[0073] The preparation process of the catalyst was the same as in Example 1, except that the reaction temperature of the catalyst for catalytic dehydrogenation of formic acid was changed to 70° C., and other conditions remained unchanged.
[0074] After analysis and testing, the gas composition after the reaction was: 0ppm CO, 50.04% H2, 49.96% CO2. The conversion rate of formic acid was 98.6%. The initial TOF of the catalyst was 6150h -1 .
[0075] Example 5
[0076] The same as Example 1, except that the amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide added in step (3) is 0.48 g, and the other conditions remain unchanged.
[0077] After analysis and testing, the initial TOF of the catalyst was 1550h -1 .
[0078] Example 6
[0079] The same as Example 1, except that the amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide added in step (3) is 0.24 g, and the other conditions remain unchanged.
[0080] After analysis and testing, the initial TOF of the catalyst was 1760h -1 .
[0081] Example 7
[0082] Same as Example 1, except that the amount of monoethanolamine borate added in step (4) is 0.18 g, and other conditions remain unchanged.
[0083] After analysis and testing, the initial TOF of the catalyst was 1460h -1 .
[0084] Example 8
[0085] The same as Example 1, except that the amount of monoethanolamine borate added in step (4) is 0.3 g, and the other conditions remain unchanged.
[0086] After analysis and testing, the initial TOF of the catalyst was 1640h -1 .
[0087] Comparative Example 1
[0088] The same as Example 1, except that there are no steps (3) and (4), and the N-Cr-MOF prepared in step (2) is directly replaced by the NPB-Cr-MOF prepared in step (5) for impregnation-reduction. The activity of the obtained catalyst is reduced at a reaction temperature near room temperature (25-30°C), and the reaction temperature is equal to that of the catalyst of the present invention only when it is greater than or equal to 50°C. This shows that if the catalyst carrier is not modified with phosphorus and boron simultaneously, it cannot meet the high activity at low temperature.
[0089] Comparative Example 2
[0090] The same as Example 1, except that step (4) is omitted, and the NP-Cr-MOF prepared in step (3) is directly replaced by the NPB-Cr-MOF prepared in step (5) for impregnation-reduction. The resulting catalyst also cannot meet the requirements of high activity at low temperatures.
[0091] Comparative Example 3
[0092] The same as Example 1, except that B modification is performed first, and then N and P modification are performed, that is, the preparation steps are: step (1), step (4), step (2), step (3), step (5). The catalyst has poor activity at near room temperature, and even at a higher temperature of 50°C, the activity is not good.
[0093] Comparative Example 4
[0094] The same as Example 1, except that N modification is performed first, and then B and P modifications are performed in sequence, that is, the preparation steps are: step (1), step (2), step (4), step (3), step (5), and the catalytic activity is reduced by about 1 / 3.
[0095] Comparative Example 5
[0096] The same as Example 1, except that in step (5), NPB-Cr-MOF is mixed with Na2PdCl4 aqueous solution and stirred at room temperature for 6 to 12 hours, then NaBH4 aqueous solution is added, reduction reaction is carried out at -5 to 5°C for 2 to 3 hours, washed, and dried to obtain a catalyst. Compared with the catalyst prepared by the present invention, the catalyst prepared by the method has a catalytic activity loss of more than half, and CO generation is detected. This is because the present invention adds Cr(NO3)3·9H2O during the impregnation reduction process and controls the reaction time, thereby reducing the particle size of the active ion palladium.
[0097] Comparative Example 6
[0098] The same as Example 1, except that there is no step (2), step (3) and step (4), the catalytic activity of the prepared catalyst is reduced by more than 90% under the reaction conditions of 25-30° C. compared with the catalyst prepared by the present invention. This indicates that if the carrier is not modified with N, P, or B, its low-temperature catalytic activity is poor.
[0099] Comparative Example 7
[0100] Compared with patent 202110958246.X, the advantage of the catalyst of the present invention is that it has better activity at near room temperature reaction temperature (25-30°C).
Claims
1. A catalyst for catalytic dehydrogenation of formic acid, characterized in that: The catalyst used for catalytic dehydrogenation of formic acid is a catalyst that uses a chromium metal organic framework material modified by nitrogen, phosphorus and boron groups as a carrier and uniformly loads nano-palladium and chromium. Wherein, according to the mass ratio, nano palladium: chromium = (1-2.5): 1; the loading rate is: the loading rate of nano palladium is 0.5-20wt%, and the loading rate of chromium is 0.5-15wt%.
2. The catalyst for catalytic dehydrogenation of formic acid according to claim 1, characterized in that By using X-ray energy spectrum analysis, the catalyst for catalytic dehydrogenation of formic acid includes the following main chemical components and the mass percentage of each component: C is 40-55%, O is 20-35%, Pd is 0.5-20%, Cr is 0.5-15%, N is 2-6%, P is 1-8%, B is 1-8%, and the balance is loss on ignition and unavoidable impurities. The percentage of each impurity is <1%.
3. The method for preparing a catalyst for catalytic dehydrogenation of formic acid according to claim 1 or 2, characterized in that: It is an impregnation-reduction method, comprising the following steps: S1: Using NPB-Cr-MOF as a carrier, adding deionized water to NPB-Cr-MOF, mixing, and ultrasonicating to obtain a uniform carrier solution; S2: Under continuous stirring, the nonahydrate chromium nitrate solution and the Na2PdCl4 solution are dropped into the carrier solution, and the reaction is continued by stirring for 2 to 3 hours. The NaBH4 solution is added and the stirring is continued for 30 to 50 minutes. The solid-liquid separation is performed, and the filter membrane with the precipitate is freeze-dried. After removing the filter membrane, PdCr-NPB-Cr-MOF is obtained.
4. The method for preparing a catalyst for catalytic dehydrogenation of formic acid according to claim 3, characterized in that: In the step S1, according to the solid-liquid ratio, NPB-Cr-MOF: water = 1 g: (200-300) mL; And / or, the ultrasonic frequency is 30-50KHz, and the ultrasonic time is 30-60min; And / or, in the step S2, the amount of chromium nitrate nonahydrate solution added is 15-25% by volume of the carrier solution, and the amount of Na2PdCl4 solution added is 18-40% by volume of the carrier solution; And / or, in the step S2, the molar concentration of the chromium nitrate nonahydrate solution is 0.01-0.035 mol / L, and the dripping rate is 0.5-3 mL / min; And / or, in step S2, the molar concentration of the Na2PdCl4 solution is 0.02-0.03 mol / L, and the dripping rate is 1-1.5 mL / min; And / or, in the step S2, the amount of NaBH4 solution added is 35-50% of the volume percentage of the carrier solution; the molar concentration of the NaBH4 solution is 0.3-0.4 mol / L; And / or, freeze drying is freeze drying at -50 to -60°C for 8 to 12 hours.
5. The method for preparing a catalyst for catalytic dehydrogenation of formic acid according to claim 3, characterized in that: The NPB-Cr-MOF is prepared by the following preparation method, which specifically comprises the following steps: (1) mixing a chromium metal organic framework material, nitric acid and sulfuric acid at -20 to 0°C and stirring for 5 to 8 hours to obtain a mixture; after the reaction of the mixture is completed, cooling, solid-liquid separation, washing the solid product with deionized water, and then vacuum drying to obtain NO2-Cr-MOF; Stannous chloride and NO2-Cr-MOF are stirred in an ethanol solution at 55-75°C for 6-10 hours, centrifuged, and the obtained solid product is washed with hydrochloric acid and ultrasonic combined with distilled water, and then dried again at high temperature and in vacuum to obtain N-Cr-MOF; (2) placing N-Cr-MOF in N,N-dimethylformamide solvent, heating and reflux at 65° C. for 30 to 40 minutes, adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and continuing to heat and reflux, reacting for more than 12 hours, removing N,N-dimethylformamide, washing with acetonitrile and water and recrystallizing to obtain precipitated NP-Cr-MOF; (3) Monoethanolamine borate (MEB) and anhydrous ethanol are mixed and stirred until the monoethanolamine borate is completely dissolved, and then NP-Cr-MOF is added and stirred evenly at room temperature. The mixture is reacted for 10 to 15 hours, and the solid-liquid separation is performed. The obtained precipitate is washed with ethanol to remove impurities, and vacuum dried to obtain NPB-Cr-MOF.
6. The method for preparing a catalyst for catalytic dehydrogenation of formic acid according to claim 5, characterized in that: In the step (1), the mass ratio of chromium metal organic framework material: nitric acid: sulfuric acid is 1: (70-112): (75-130); the cooling temperature is -10-5°C; the vacuum drying is performed at a vacuum pressure of 0.95-0.98 atm and a temperature of 40-70°C for 8-16 hours; According to the mass ratio, stannous chloride: NO2-Cr-MOF = (25-85): 1; according to the solid-liquid ratio, stannous chloride + NO2-Cr-MOF: ethanol is 1g: (5.5-8.5)mL; the temperature of high-temperature vacuum drying is 130-170°C; And / or, in the step (2), the amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide added is 30-60% by mass of N-Cr-MOF; And / or, in the step (3), the mass ratio of monoethanolamine borate (MEB):NP-Cr-MOF=(0.3-0.5):1; the amount of anhydrous ethanol used is based on the amount that can fully dissolve the monoethanolamine borate.
7. The method for preparing a catalyst for catalytic dehydrogenation of formic acid according to claim 5, characterized in that: The chromium metal organic framework material is prepared by a hydrothermal method, and the specific preparation method is as follows: Step 1: Mix chromium salt, terephthalic acid, hydrofluoric acid and deionized water, add into a high pressure reactor, react at 160-230° C. for 8-12 hours, cool naturally to room temperature, separate solid from liquid, wash, and obtain a solid product; Step 2: placing the solid product in an ammonium fluoride solution, soaking it, and centrifuging it to obtain a solid substance; washing the solid substance with deionized water to remove impurities, and vacuum-activating it to obtain a chromium metal organic framework material, recorded as Cr-MOF.
8. The method for preparing a catalyst for catalytic dehydrogenation of formic acid according to claim 7, characterized in that: In the step 1, the molar ratio of terephthalic acid, chromium in chromium salt, hydrofluoric acid, and deionized water is 1:(1-3):(0.12-0.35):(25-30); And / or, the chromium salt is selected from one or more of CrCl3, Cr2(SO4)3·6H2O, Cr(NO3)·9H2O, C6H9O6Cr; And / or, in the step 2, the molar concentration of the ammonium fluoride solution is 0.5-2 mol / L, and according to the solid-liquid ratio, the solid product: ammonium fluoride solution = 1 g: (6-10) mL; And / or, in the step 2, the soaking temperature is 60-90°C, and the soaking time is more than 24 hours; and / or, the centrifugal speed of centrifugal separation is 6000-10000r / min, and the centrifugal time is 10-15min; and / or, the vacuum activation temperature is 150-180°C, and the vacuum activation time is 8-20h.
9. Use of the catalyst for catalytic dehydrogenation of formic acid according to claim 1 or 2 or the catalyst for catalytic dehydrogenation of formic acid prepared by the preparation method according to any one of claims 3 to 8, characterized in that: The catalyst for catalytic dehydrogenation of formic acid is used for catalytic dehydrogenation of formic acid, which comprises the following steps: The catalyst used for catalytic dehydrogenation of formic acid is used as a catalyst to carry out continuous catalytic dehydrogenation of formic acid. The reaction conditions are: stirring the reaction at 25-70° C. and normal pressure, collecting the produced hydrogen, and continuously adding formic acid dropwise during the reaction. The dropping speed of formic acid is converted according to the amount of hydrogen produced, that is, the amount of formic acid consumed in producing hydrogen is the amount of formic acid added.
10. The use of the catalyst for producing hydrogen by catalytic pyrolysis of formic acid according to claim 9, characterized in that: The catalyst used for formic acid catalytic pyrolysis to produce hydrogen is used for formic acid catalytic pyrolysis to produce hydrogen, and its TOF is 600-6150h -1 The hydrogen selectivity was 100% and the formic acid conversion rate was 92-98.6%. After being reused three times, the formic acid conversion rate did not decrease, and the CO content in the product was <0.5ppm.
Citation Information
Patent Citations
A Cr-based MOF carbon material catalyst co-doped with palladium nanoparticles, its preparation and application in formic acid hydrogen production.
CN113731502B